PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMGAMES TOURNAMENT) TERHADAP PENGUASAAN KONSEP MATERI ELASTISITAS KELAS XI MIPA SMA NEGERI 51 JAKARTA - Raisandy Aziz (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2022)
The objective of this research is to analyze the improvement in quality values between classes that use the Cooperative Learning Method tipe TGT (Team Games Tournament) with the DirectInstruction class at Jakarta 51 High School grade XI MIPA conduct research from april until may 2019. This research method used the quantitative research methods type of quasi experimental thatfocus on the mastery of Elasticity concept in science in seeing the influence of cooperative learning models using the TGT type. The results of the study are described using a purposive sampling that compares the differences in 2 (two) classes, namely the experimental class through the Team Games Tournament learning model and the control class through the Direct Learning model in students and then measures the mastery level of Elasticity concept.